Anisotropy in the plastic flow properties of single-crystal alpha titanium determined from micro-cantilever beams - Gong, J; Wilkinson, A (2009)
Single-crystal micro-cantilever beams were manufactured from a polycrystalline commercially pure Ti sample using a focused ion beam. The cantilevers were approximately 5 μm wide and 30 μm long. A nano-indenter was then used to conduct micro-bending tests. Slip systems are selectively activated in these α-Ti beams by varying the crystal orientation along the beam. Increasing end deflections, from 1 to 8 μm, were applied to a series of similarly oriented cantilevers to show the progressive development of deformation. Load drops associated with strain bursts were seen in the mechanical response of some of the plastically deforming cantilevers. These appear to correlate with the formation of intense slip bands in the cantilevers. A crystal plasticity-based finite element model was applied to simulate the bending behaviour of single-crystal beams in the tested crystal orientations. Critical resolved shear stresses of 181 MPa for 〈a〉 on the prismatic, 474 MPa for 〈c + a〉 on the pyramidal and 209 MPa for 〈a〉 on the basal planes were determined via the reverse process of fitting the model load-displacement curves to experimental ones. © 2009 Acta Materialia Inc.